Agronomic Factors Affecting Dryland Grain Sorghum Maturity and Production in Northeast Colorado. (1st November 2014) - Sauer, Sally M.; Johnson, Jerry J.; McMaster, Gregory S.; Vigil, Merle F.
Abstract : Grain sorghum [ Sorghum bicolor (L.) Moench] is an important dryland crop in southeastern Colorado, but expansion into northeastern Colorado is thought to be limited due to the shorter growing season. The study examined whether sorghum production could be expanded into northeastern Colorado. A 2‐yr study in northeastern Colorado at Akron (2010, 2011), Fort Collins (2011), and Stratton (2010) investigated row orientation, seeding rate, and row spacing effects for three hybrids within early to medium‐early maturity classes on the time to physiological maturity and grain yield. All treatments reached physiological maturity in the four trial environments. Hybrid selection and seeding rate significantly impacted the thermal time to reach physiological maturity. The medium‐early hybrid (5745) matured significantly later than the early maturity hybrids (88P68 and DKS29‐28). The seeding rate of 20 seeds m −2 matured significantly earlier than 11 seeds m −2, which matured much earlier than 3 seeds m −2 . Row orientation and row spacing did not influence maturity. Yields were generally acceptable across all environments, hybrids, and agronomic treatments, and average yields among environments ranged from 1690 to 4845 kg ha −1 . Probabilities of the hybrids reaching maturity were high at Akron and Stratton (at least 62 and 86%, respectively, for the latest simulated planting date), but low for Fort Collins (highest of 75% for the earliest simulated planting date). Grain sorghum can successfully be grown in northeast Colorado, especially if planting early maturity hybrids using 0.76 m row spacing at a seeding rate close to 11 seeds m −2 .